MEREKAM KISAH KUSDONO RASTIKA MELALUI FILM DOKUMENTER EKSPOSITORI “BERKACA PADA LUKISAN KACA KUSDONO RASTIKA” - Widhi Nugroho; Cito Yasuki Rahmad (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
The condition of disabled artists in Indonesia has a variety of artistic fields in their activities. They pursue several fields of art such as music, painting, literature, theater, and dance. The variety of disabilities they experience also varies. They use all their abilities to keep working. The works of artists with disabilities in Indonesia (in general) show the presence of their experience as people with disabilities and some are purely artistic works without showing that a creator is a person with a disability. Kusdono Rastika is one of the many Cirebon glass painters. Glass painting is unique in its way, both the media used and the technique. Unfortunately, from this uniqueness, the fate of current glass painting artists like Kusdono Rastika can be said to be far from the "beauty reflection" of the colors emitted. The lack of appreciation in the form of exhibitions of works and media exposure, makes Kusdono and his glass paintings seem to have “lost their luster” in the repertoire of contemporary Indonesian painting. Qualitative descriptive methods in the form of notes, documentation, and archiving of Kusdono Rastika's story can be used as an example of how determination and struggle to advance glass painting towards independence and economic sovereignty can be seen through this expository style documentary.